Effects of deep cryogenic treatment on machinability, hardness and microstructure in dry turning process of tempered steels. (August 2021) - Kam, Menderes
This study investigated the effects of Deep Cryogenic Treatment (DCT) on machinability, hardness, and microstructure in dry turning process of AISI 4140 (48-51 HRc) tempered steels with ceramic cutting tools on the surface roughness (Ra). DCT process of steels has shown significant improvement in their mechanical properties. In this context, experiments were made with Taguchi L16 method and optimum values were determined. Three different values for each control factors as: different heat treated samples, cutting speeds (160, 200, 240, 280 m/min), feed rates (0.08, 0.12, 0.16, 0.20 mm/rev) were selected. As a result, the lowest Ra value was found to be 0.159 µm for the DCTT36 sample at a cutting speed of 240 m/min, a feed rate of 0.08 mm/rev. The optimum Ra value was the lowest for the DCTT36 sample compared to the other samples as 0.206 µm. The hardness values of the micro and macro were highest for the DCTT36 sample. Microstructural point of view Scanning Electron Microscopy (SEM) point of view, the DCCT36 sample showed that best results owing to its homogeneity. It was concluded that lower Ra values can be obtained with ceramic cutting tool in dry turning experiments according to the studies in the literature review. It is thought to be preferred as an alternative to cylindrical grinding process due to lower cost.